Determination of the cycle threshold value of the Xpert Xpress SARS-CoV-2/Flu/RSV test that corresponds to the presence of infectious SARS-CoV-2 in anterior nasal swabs - Ryan F. Relich; Kayla Van Benten; Guang-Sheng Lei; Christopher M. Robinson; Mariel Carozza; Malaya K. Sahoo; ChunHong Huang; Daniel Solis; Mamdouh Sibai; Christopher A. Myers; Cynthia Sikorski; Caroline Balagot; et al. (Microbiology Spectrum, 2024)
ABSTRACTDespite having high analytical sensitivities and specificities, qualitative SARS-CoV-2 nucleic acid amplification tests (NAATs) cannot distinguish infectious from non-infectious virus in clinical samples. In this study, we determined the highest cycle threshold (Ct) value of the SARS-CoV-2 targets in the Xpert Xpress SARS-CoV-2/Flu/RSV (Xpert 4plex) test that corresponded to the presence of detectable infectious SARS-CoV-2 in anterior nasal swab samples. A total of 111 individuals with nasopharyngeal swab specimens that were initially tested by the Xpert Xpress SARS-CoV-2 test were enrolled. A healthcare worker subsequently collected anterior nasal swabs from all SARS-CoV-2-positive individuals, and those specimens were tested by the Xpert 4plex test, viral culture, and laboratory-developed assays for SARS-CoV-2 replication intermediates. SARS-CoV-2 Ct values from the Xpert 4plex test were correlated with data from culture and replication intermediate testing to determine the Xpert 4plex assay Ct value that corresponded to the presence of infectious virus. Ninety-eight of the 111 (88.3%) individuals initially tested positive by the Xpert Xpress SARS-CoV-2 test. An anterior nasal swab specimen collected from positive individuals a median of 2 days later (range, 0–9 days) tested positive for SARS-CoV-2 by the Xpert 4plex test in 39.8% (39/98) of cases. Of these samples, 13 (33.3%) were considered to contain infectious virus based on the presence of cultivable virus and replication intermediates, and the highest Ct value observed for the Xpert 4plex test in these instances was 26.3. Specimens that yielded Ct values of ≤26.3 when tested by the Xpert 4plex test had a likelihood of containing infectious SARS-CoV-2; however, no infectious virus was detected in specimens with higher Ct values.IMPORTANCEUnderstanding the correlation between real-time PCR test results and the presence of infectious SARS-CoV-2 may be useful for informing patient management and workforce return-to-work or -duty. Further studies in different patient populations are needed to correlate Ct values or other biomarkers of viral replication along with the presence of infectious virus in clinical samples.